Seagrass beds as the buffer zone for fish biodiversity in coastal water of Bontang City, East Kalimantan, Indonesia - ADITYA IRAWAN; SUPRIHARYONO SUPRIHARYONO; JOHANNES HUTABARAT; AMBARIYANTO AMBARIYANTO (Society for Indonesian Biodiversity, 2018)
Irawan A, Supriharyono, Hutabarat J, Ambariyanto. 2018. Seagrass beds as the buffer zone for fish biodiversity in coastal water of Bontang City, East Kalimantan, Indonesia. Biodiversitas 19: 1044-1053. The purpose of this study was to demonstrate the importance of seagrass beds as a buffer zone for fish biodiversity in a coastal ecosystem. The sampling of seagrass and fish were done in seagrass beds associated with mangrove (ST1) and coral reef (ST2). Sampling period was executed from May 2011 to May 2017. Sampling was done on the lowest tide with a six-month interval. Seagrass sampling was carried out using line transect, and fish sampling was performed using set net (belat local name) operated by local fisherman. The results showed that seagrass beds at ST1 composed of C. rotundata and E. acoroides and that at ST2 composed of C. rotundata, E. acoroides, H. pinifolia, H. minor and T. hemprichii. The total number of individual was 42574 divided into 112 fish species. There were 17 species (population: 15.18%) associated explicitly with ST1 and 39 species (population: 34.82%) specifically associated with ST2 while 56 fish species (population: 50.0%) were prevalently spread in both stations. This research proved the existence of seagrass beds as a buffer zone for fish biodiversity.